The Association Between Internet Gaming Disorder and Sensation Seeking Among Arab Adolescents - Hamid, Mohamed S.; Abo Hamza, Eid; Hussain, Zaheer; AlAhmadi, Aisha (Frontiers in Psychiatry, 2022)
Research on internet gaming disorder (IGD) has increased considerably over the last decade. Although most IGD research has focused on Western or South Asian samples, it is critical to understand and assess this disorder among other populations. The present study investigated the association between IGD and sensation seeking among Arab adolescents. An online survey consisting of the short internet gaming disorder short scale (IGDSS) and brief sensation seeking scale (B-SSS) was completed by 260 participants (mean age = 14.61, SD = 2.43). The results showed that sensation seeking behaviours were associated with higher gaming hours and greater chances of exhibiting internet gaming disorder. The findings support the current perspective of understanding this disorder from a disease framework as it highlights the relevance of behavioural components in gaming addiction. Importantly, the results will further aid the development of reliable diagnosis and efficacious treatments within clinical practices.